Structural and magnetic properties of Y1-xDyxFeO3 multiferroics. (2021) - Padmasree, G.; Shravan Kumar Reddy, S.; Pavan Kumar, N.; Yadagiri Reddy, P.; Gopal Reddy, Ch.
Abstract: Y1-x Dyx FeO3 (x = 0.0, 0.2, 0.4, 0.6 and 0.8) multiferroic materials are prepared by sol–gel method. The effect of Dy doping on the structural and magnetic properties of YFeO3 has been investigated in this paper. X-ray diffraction plots indicate that all the samples are crystalline and possess orthorhombic structure. The morphological studies show that samples possess non uniform grain size and grains are irregular in shape. Magnetic measurements suggest that substitution of Dy +3 ions in place of Y +3 ions effectively enhances the magnetization of YFeO3 . This enhancement may be due to the additional Dy-Dy interactions, Dy-Fe interactions and Fe-O-Fe superexchange bond caused by the distortion of crystal structure.